Palatal bone block: A predictable bone augmentation technique for restricted maxillary defect - Farhan Durrani; J P Vishnu; Aabida Taslim; Fouzia Imran; Ekta Kumari; Aishwarya Pandey (Wolters Kluwer Medknow Publications, 2023)
Bone grafting for implant dentistry depends on bone quality, quantity, and biological principles for good outcome. Autogenous bone as donor remains the gold standard among all the available materials. However, it carries unpredictable morbidity and need for different surgical sites. In our report, we describe a simplified approach in bone augmentation for restricted maxillary atrophic defect within the same surgical site as a harvesting site. The method can be an alternative for different intraoral surgical harvesting sites. The patient's left maxillary central incisor before treatment had a large bony defect which was reconstructed though single site approach of augmentation. The implant-supported restoration with healthy periodontium around even after 2 years of review looks promising. The approach can be an alternative for different intraoral surgical sites.